The effects of social policies on the working careers of Europeans - Agar Brugiavini; Giuseppe De Luca; Thomas E. MaCurdy; Guglielmo Weber (Institute for Fiscal Studies (IFS), 2020)
We analyse the pattern of work and other labour market states, such as unemployment and out-of-labour-force, over the life course, by making use of a long retrospective panel of older Europeans. Based on stochastic simulations of a reduced form transition probability model, we document to what extent social policies over the life course affect employment trajectories both in the long run and in the short run. We focus on two types of reforms that have taken place in various European countries over the lifetime of the panel participants: increases in compulsory school age and increases in pension eligibility age.
Keywords: J22; J26; J64; 330; Employment histories; path dependence; education policies; pension reforms